Deteksi Dini Kadar Gula Darah Sewaktu, Kolesterol Total dan Asam Urat pada Masyarakat Kecamatan Deli Tua - Nofi Susanti; Ikhwan Ikhwan (FKM UIN Sumatera Utara Medan, 2022)
Currently, Indonesia is fighting the double burden of diseases, namely infectious diseases and non-communicable diseases. One way to control non-communicable diseases is by reducing and controlling risk factors through early detection (screening). This study aims to find out the picture of time blood sugar levels, total cholesterol, and uric acid in the deli Tua community. The type of research used is a survey with a cross-sectional design conducted in Deli Tua District, Deli Serdang North Sumatra Province in February 2020. The sample of this study was 70 respondents with details of 63 respondents checking time blood sugar levels 39 respondents checked total cholesterol levels and 56 respondents checked uric acid levels. Sample take it using accidental sampling techniques with instruments in the form of lancet pens, alcohol swabs, GCU meters branded Easy Touch, and glucose, cholesterol, and urine acid strips. The study used univariate analysis. with cross-tabulation (crosstab). Based on the results of research average time blood sugar levels in the Deli Tua community is in the normal category of 145.70 mg /dL, total cholesterol levels in the ABA (Upper Threshold) category reach 201.79 mg /dL and uric acid levels in the normal category reach 5.84 mg /dL. The local health center can activate Posbindu cadres and carry out early detection so that the risk factors for non-communicable diseases can be controlled.